Analysis of the Mechanism of PGLP-1 Inhibiting Gluconeogenesis Based on Whole Transcriptome Sequencing - Gao, Huashan; Yu, Hao; Tong, Weishuang; Fan, Weiwei; Mai, Yanqun; Feng, Wenpo; Qiu, Yuanhao (Current Pharmaceutical Biotechnology, 2025)
<span class=
Keywords: PI3K-Akt signaling